1964
DOI: 10.2307/2440063
|View full text |Cite
|
Sign up to set email alerts
|

A Cytogenetic Analysis of Certain Polyploids in Grindelia (Compositae)

Abstract: Two diploid taxa, Grindelia procera and G. camporum, and 3 tetraploid ones, G. camporum, G. hirsutula, and G. stricta, have been studied to ascertain their interrelationships. Meiosis in diploid parental strains was regular, the common chromosome configuration being 5 rod bivalents and 1 ring bivalent. The average chiasmata frequency per chromosome was 0.60. Pollen fertility was about 90% in all strains examined. Diploid interspecific hybrids had normal meiosis with an average chiasmata frequency of 0.56 per c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

1970
1970
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 6 publications
(8 reference statements)
0
22
0
Order By: Relevance
“…There are 15 species in Argentina, eight of which are endemic (Cabrera, 1931;Ariza Espinar, 1976;Bartoli & Tortosa, 1994). Within the genus Grindelia, diploid (2n"12), tetraploid (2n"24) and hexaploid (2n"36) species, or populations within the same species, have been found (Schnack & Covas, 1947;Dunford, 1964;Hunziker et al, 1989;Bartoli et al, 1990Bartoli et al, , 1993.…”
Section: Introductionmentioning
confidence: 99%
“…There are 15 species in Argentina, eight of which are endemic (Cabrera, 1931;Ariza Espinar, 1976;Bartoli & Tortosa, 1994). Within the genus Grindelia, diploid (2n"12), tetraploid (2n"24) and hexaploid (2n"36) species, or populations within the same species, have been found (Schnack & Covas, 1947;Dunford, 1964;Hunziker et al, 1989;Bartoli et al, 1990Bartoli et al, , 1993.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the two ecotypes are reproductively isolated under natural conditions, due to little overlap in flowering time and to selection against immigrants from the other ecotype [18]. As in Grindelia [33], intrinsic postzygotic isolation between ecotypes was not found [18].…”
Section: Discussionmentioning
confidence: 98%
“…They vary in stature (from 30 to 200 cm tall), woodiness (from not at all woody to having woody branches more than 1 m long), head shape and size, leaf and phyllary morphology, degree of succulence, amount of resin, and flowering time (from early summer to fall). These differences appear to be genetic, as they persist when the plants are grown in a common garden [33], [34]. Although there is clearly much morphological variation within Pacific Grindelia , and plants from two different habitats often have striking morphological differences, it is generally very difficult to draw clear boundaries between putative taxa when they are examined across their entire ranges.…”
Section: Introductionmentioning
confidence: 99%
“…indicate another way in which genetic material may be exchanged between diploids and tetraploids, the formation of unreduced gametes in diploids being the first noted (Dunford, 1964). indicate another way in which genetic material may be exchanged between diploids and tetraploids, the formation of unreduced gametes in diploids being the first noted (Dunford, 1964).…”
Section: O"y1cpismentioning
confidence: 98%
“…which have been analyzed cytologically the common meiotic chromosome configuration is 12 bivalents, or 10 bivalents and 1 quadrivalent, or 8 bivalents and 2 quadrivalents, whereas Grindelia diploids (2n = 12) normally form 6 bivalents (Whitaker and Steyermark, 1935;Raven et al, 1960;Dunford, 1964). On the basis of bivalent and quadrivalent formation in hybrids obtained by crossing diploid and tetraploid taxa of Grindelia from California, as well as diploids X diploids, and tetraploids X tetraploids, it was concluded that Grindelia tetraploids were autopolyploids that had undergone some diploidization (Dunford, 1964).…”
Section: In the Tetraploids (2n = 24) Of Grindeliamentioning
confidence: 99%